2014
DOI: 10.2478/pjfns-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Novel Processing Techniques on Glucosinolates and Membrane Associated Myrosinases in Broccoli

Abstract: longed shelf-life by inactivation of micro-organisms and enzymes. HP/HT can at temperatures above 50 o C lead to pasteurization using pressure levels from 250-500 MPa [Wilson et al., 2008], while sterilization can be obtained with HP at temperatures higher than 70 o C . Focus is thus on the application of HP in combination with high temperatures (HT), which may lead to tissue compression, cell wall breakage and cell membrane disruption, depending on the HP and HT levels as well as the type of vegetable or frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 42 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…It is, anyway, more likely that the observed degradation of the glucosinolates is a result of a fast interaction with the active enzyme myrosinase, as shown in previous studies (Bellostas et al, 2008). The pattern observed in glucosinolate concentration related to pressure is similar to the results obtained when broccoli heads were HP-treated for 10 min at different pressure levels (Frandsen et al, 2014), where a decrease in glucosinolate content was observed at 300 MPa, followed by an increase at 700 MPa.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
See 2 more Smart Citations
“…It is, anyway, more likely that the observed degradation of the glucosinolates is a result of a fast interaction with the active enzyme myrosinase, as shown in previous studies (Bellostas et al, 2008). The pattern observed in glucosinolate concentration related to pressure is similar to the results obtained when broccoli heads were HP-treated for 10 min at different pressure levels (Frandsen et al, 2014), where a decrease in glucosinolate content was observed at 300 MPa, followed by an increase at 700 MPa.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…In these studies, HP parameters had an impact on the myrosinase activity and the extent of glucosinolate hydrolysis. The effects from the HP treatment may however be blurred by pre-processing effects on enzymes and bioactive compounds upon disruption of (Frandsen et al, 2014). This stresses the importance of investigating the myrosinase-glucosinolate interactions in a well-defined and homogenous plant matrix in order to provide basic knowledge of the HP impact on the health beneficial compounds from cruciferous vegetables.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 1 more Smart Citation
“…Compounds such as sinigrin, gluconapin, progoitrin, and indole GSLs (glucobrassicin, neoglucobrassicin) are cited as imparting bitterness in crops such as broccoli, and other varieties of B. oleracea ; however, this effect is not universal, as taste panelists do not uniformly detect or describe these as bitter in isolation (Table ) . This suggests that some individuals may be “non‐tasters” or “bitter blind” for these GSL compounds, as with PROP and PTC.…”
Section: Bitter Taste Of Glucosinolates and Isothiocyanatesmentioning
confidence: 99%
“…In a recent study, Frandsen et al [21] evaluated the effect of PEF treatment conditions on broccoli glucosinolates and associated myrosinase isoenzymes. The study could not find differences in glucosinolate contents related to the type of waveform and treatment time.…”
Section: Phenolic Compoundsmentioning
confidence: 99%